CONCEPTUAL PROVISIONS OF THE STATE POLICY FOR ENTREPRENEURSHIP DEVELOPMENT IN THE PRODUCTION SECTOR OF THE ECONOMY - FEDORCHUK, Sergii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The study analyzes the issues of forming and implementing state policy to stimulate the development of the entrepreneurial sector of the national economy. The focus of attention is on the issues of regulating the development of entrepreneurship directly in the production sector. Therefore, the purpose of the study is to develop conceptual provisions of the state policy for the development of entrepreneurship in the manufacturing sector of the economy. It is shown that in modern conditions of globalization and economic instability, the development of entrepreneurship in the manufacturing sector is becoming a key factor in ensuring economic growth, competitiveness and sustainability of the national economy. It has been proven that the development of entrepreneurship in the manufacturing sector of the economy directly depends on state policy, which is a key element of the functioning of society and covers a wide range of aspects and characteristics that form the basis of strategically oriented public administration. The approaches to setting priorities and implementing strategic goals that meet the interests of citizens and the development of the middle, in particular, entrepreneurial, class are summarized. The analysis of entrepreneurial activity in the woodworking industry emphasizes the importance of strategic potential, which includes personnel, production, financial and other aspects necessary for the sustainable development of enterprises. Effective strategic management focused on innovation, optimization of production processes and greening of activities can significantly increase the competitiveness of the industry, promote regional economic development and adaptation to changing market conditions. State policy for the development of entrepreneurship in the manufacturing sector is a complex and multifaceted process that combines various conceptual models, such as neoclassical, Keynesian and institutional, the consideration of which allows forming a rational structure of instruments and means of state policy.
Keywords: entrepreneurship; entrepreneurial sector; entrepreneurial activity; development; manufacturing sector; public policy; public regulation